Measurement of Medication Adherence Behavior in Type 2 Diabetes Mellitus Patients Using Probabilistic Medication Adherence Scale (ProMAS) - Dini Ayu Rahmawati; Susi Ari Kristina; Anna Wahyuni Widayanti (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Diabetes mellitus is a chronic disease that requires long-term treatment, which affects medication adherence. Adherence measurement can be done using a questionnaire like the Probabilistic Medication Adherence Scale (ProMAS). This study aims to determine the relationship between demographic factors and medication adherence scores in patients with diabetes mellitus. The research uses a quantitative research approach with a cross-sectional design. The convenience sampling method was used to select 112 respondents between January and April 2023 at various primary healthcare facilities in the Special Region of Yogyakarta. The ProMAS scoring results were based on the highest rankings, with 42.8% of respondents having a moderate-to-high adherence level, 41.1% of respondents having a high adherence level, 15.2% of respondents having a moderate-low adherence level, and 0.9% of respondents having a low adherence level. Diabetes mellitus patients in Yogyakarta show a high level of medication adherence. The most frequent non-adherent behavior was found in 4 questions: respondents forgot to take or inject medication (61.61%); respondents took or injected medication (one of them) slower than usual schedule (55.36%); respondents did not always take or inject medication at the same time every day (62.5%); and respondents forgot to take or inject medication at least once in the past month (58.04%). The statistical analysis indicates no relationship between demographic characteristics, the total number of medications, and the total frequency of medication with adherence levels. This indicates that diabetes mellitus patients with low or high adherence levels are unaffected by the above factors.